One shot of hyaluronic acid in advanced knee osteoarthritis: postmarketing clinical follow-up for real-world evidence in a pain unit - Pilar Acín; Amparo Santamaría; Elena Gómez-Rubio; Pilar Coronel Granado (BMC Musculoskeletal Disorders, 2025)
Abstract Background this study aims to assess the real-world efficacy and safety of one shot of intraarticular (IA) hyaluronic acid (HA) in patients with advanced knee osteoarthritis (OA), in accordance with the requirement of the new EU Regulation on medical devices to monitor the safety and efficacy of throughout their life cycle. Methods observational, cross-sectional and retrospective study in a cohort of patients with advanced knee OA treated in a Pain Unit with a single injection of IA HA between January 2021 and December 2022. Efficacy was assessed at 6 months using the Visual Analogue Scale (VAS) for pain, and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for pain, stiffness and function. The Research Ethics Committee of the Autonomous Community of Aragon (CEICA) approved the study. Patient’s data were pseudonymized. Results the study included a cohort of 30 patients (mean age 73.1, 63.3% female, 66.7% retired). At 6 months, patients showed 51.3% and 52.2% reduction in pain (VAS and WOMAC, respectively), 44.9% improvement in function and 60% improvement in stiffness. In addition, 83.3% of patients showed improvement ≥ 20% according to VAS and 80% of patients according to total WOMAC. No adverse events were informed. Conclusion the results support the use of IA HA as an effective and safe treatment for advanced knee OA, providing significant improvements in pain, stiffness, and function over six months. Future research should include larger populations.